Regional Shift to Bahasa Indonesia: ‘Old Vernacular’ In A New Identity - Kleden-Probonegoro, Ninuk; Imelda (RMPI-BRIN, 2015)
The Gamkonora people are an ethnic group in Indonesia whose members have an outstanding linguistic ability: they are able to speak more than two languages, that is, two or more of Gamkonora, Ternatan-Malay, Ternate, and Bahasa Indonesia. The use of these languages is related to the residual traces of the powers that have ruled the area in the history of North Maluku: the Ternate sultanate, European colonialists and Indo nesian central government since independence. Reflecting on the current language behaviour of the Gamko noran younger generation, which tends to be the Indonesian language (read Malay); the authors question how far the Gamkonoran’s Indonesian language ability has influenced their Gamkonoran language and culture. Through ethnographic studies, the authors found that two languages—Indonesian and Gamkonoran—have different roles in their culture. Therefore, the language shift to Bahasa Indonesia by Gamkonoran youth will not replace the Gamkonoran language because the use of their tribal language is supported by their traditional institutions.